EVALUASI PROGRAM PENCATATAN AKTA KEMATIAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA SEMARANG - Purwanto, Shahnaz Dyah; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2018)
The program of recording the death certificate by the Population and Civil Registration Office of the City of Semarang is one of the steps taken by the Semarang City Government to organize and discipline the population documents of the Semarang City community. The role of the government, especially the Semarang Population and Civil Registration Service, is very important in the success of the death certificate registration program. This study aims to evaluate the results of the program of recording the death certificate in the Semarang City Population and Civil Registration Service and knowing the obstacles and driving the program. The theory used in this study is the theory of William Dunn who has five indicators in conducting policy evaluation activities. The five indicators are effectiveness, efficiency, adequacy, leveling, responsiveness. Based on the results of the study showed that the level of achievement of the principle of recording death certificates in the city of Semarang was still low when compared to other programs related to population documents, which amounted to 31.51%. Found things - things that hinder the running of the program namely lack of adequate communication and human resources. The recommendation that can be given is to increase human resources and improve communication patterns.